Antimicrobial, Antioxidant, Hemolytic Activities and Toxicity of Ethyl Acetate Extract From an Unidentified Coral-Associated Fungus, Aspergillus brevipes RK06 - Nofiani, Risa; Kurniadi, Rio; Ardiningsih, Puji (Indonesian Journal of Cancer Chemoprevention, 2011)
Marine fungi are one of the potentialÃÂ  and prolific sources to produce unique and novel structure of bioactive compounds. The aim of this research was to explore the biological activities potency from ethyl acetate extract of Aspergillus brevipesÃÂ  RK06. A. brevipesÃÂ  RK06 was successfully isolated from an unidentified coral from Randayan Island, Kalimantan Barat. TheÃÂ  extract inhibited the oxidation of linoleic acid (Ferric thiocyanate assay) with a lipid peroxidation inhibition value of 28.44%. The IC50 value of the extract for brine shrimp lethality test was 34.19ug/mL. The hemolytic percentage of the extract for hemolysis on cow erythrocytes was 5.21%. The extract showed a growth inhibition againstÃÂ  Klebsiella pneumonia,ÃÂ  Pseudomonas aeruginosa, and Staphylococcus aureus. Based on the assays, the extract showed a potential citotoxity and both low antioxidant and hemolytic activities. ÃÂ  Key words: antioxidant, hemolytic activity, antimicrobial, toxicity,ÃÂ  Aspergillus brevipes RK06